Review of the New World genus Draeculacephala Ball (Hemiptera: Cicadellidae: Cicadellinae) from Mexico, with description of a new species - Blanco-Rodríguez, E.; Pinedo-Escatel, J.a. (Zootaxa, 2022)
The taxonomy of the leafhopper genus Draeculacephala Ball in Mexico is revised. A new species, D. quetzalcoatli sp. nov., is described and illustrated from Chiapas state. In addition, D. albipicta Dietrich is recorded for first time occurring in the country. Eight species are recognized, and updated distribution data are provided. A key to all Mexican species is also given.